Vigilância de infecção de sítio cirúrgico pós-cesariana: metodologia alternativa utilizando a tecnologia de whatsApp - Guilherme Augusto Armond (2021)
Introduction: Brazil, in recent decades, is considered one of the countries with the highest occurrence of cesarean sections in the world. Caesarean section is the most important risk factor for puerperal infections, especially surgical site infection (SSI). The short postoperative period after cesarean section makes it difficult to accurately assess the risk of SSI. SSIs are generally underestimated in incidence studies, since many of them occur after hospital discharge. Surveillance, in most hospitals, is restricted to patients until the moment of their discharge. Studies demonstrate the need to perform post-discharge surveillance in patients undergoing cesarean section, in order to obtain more accurate SSI incidence rates in order to reduce the underreporting of these infections. Objective: Validate the implementation of active surveillance of Surgical Site Infection (SSI) in cesarean section after hospital discharge, using an active search methodology combined with the use of WhatsApp technology. Methodology: The database of the Infection Control Service of the hospital under study from January 1 to November 30, 2019 was used and all patients undergoing cesarean section who had the WhatsApp application were evaluated. Contact with the patient through the WhatsApp application was made between the 21st and 30th postoperative day. Results: 2,678 cesarean sections were performed and 2,626 patients were evaluated. Of these, 1,780 had a telephone, of which 1,741 received messages via WhatsApp. The success rate of using WhatsApp for post-discharge contact with surgical patients was 67%. Of the 64 SSIs notified, 61% (n = 39) were diagnosed only by the active search performed during the patient's hospitalization and readmission and 39% (n = 25) through the use of WhatsApp. The incidence rate of SSI in cesarean section was 2.4%. Superficial SSI accounted for the highest percentage (56%), followed by endometritis (36%) and profound (8%). 64% of superficial SAIs were notified by surveillance by WhatsApp. The use of WhatsApp in the surveillance and diagnosis of SSI in cesarean section showed 100% sensitivity 99.8% specificity. Conclusion: The WhatsApp surveillance method of SSI by cesarean section after hospital discharge proved to be viable as it is a low-cost, easy-to-handle and low-cost methodology and little time spent by Infection Control Service professionals. It should be considered as a complementary method to surveillance during hospitalization to obtain post-cesarean SSI rates with greater accuracy